2014
DOI: 10.1080/09540121.2013.873764
|View full text |Cite
|
Sign up to set email alerts
|

Mediating effects of social support on depression and quality of life among patients with HIV infection in Taiwan

Abstract: Few empirical studies have evaluated the mediating effects of quality of life (QoL) among people living with HIV/AIDS (PLWHA). The purposes of this study were to identify the predictors of QoL and to test the mediating effects of social support on depression and QoL among patients enrolled in an HIV case-management program in Taiwan. A cross-sectional, descriptive correlation design collected data from 108 HIV-infected individuals. Individuals were assessed using the Beck Depression Inventory II, the short ver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
13
1
4

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(21 citation statements)
references
References 39 publications
3
13
1
4
Order By: Relevance
“…The finding was consistent with the study of Li Song and others, as the study findings showed that QOL was significantly and positively correlated with both social support and the initiation of highly active antiretroviral therapy (HAART), which can improve their QOL (Hou et al . , Li et al . ).…”
Section: Discussionmentioning
confidence: 95%
“…The finding was consistent with the study of Li Song and others, as the study findings showed that QOL was significantly and positively correlated with both social support and the initiation of highly active antiretroviral therapy (HAART), which can improve their QOL (Hou et al . , Li et al . ).…”
Section: Discussionmentioning
confidence: 95%
“…Em todos os casos, o desenho utilizado foi de natureza quantitativa e descritiva, com exceção de um deles, que propôs uma metodologia qualitativa-quantitativa 28 . Existe uma alta frequência de estudos transversais, um total de 18 artigos que representam 81,8% de todos os documentos estudados 8,9,[13][14][15][16][17][18][19][20][21][22][23][24][25][26][27]29 .…”
Section: Resultsunclassified
“…Este é o caso do determinante da qualidade de vida assistência social, que com uma aparição em 8 artigos (36,3%) é o resultado que mais vezes foi identificado 8,9,[11][12][13][14][15]23 . Com 7 artigos (31,8%) segue-se depressão 8,9,12,13,17,18,19 e estigma 8,9,12,[14][15][16]26 . A adesão é outro determinate da qualidade de vida das pessoas vivendo com HIV que foi identificado em um total de 5 artigos (22,7%) [19][20][21][22]26 .…”
Section: Resultsunclassified
See 2 more Smart Citations